Intra-annual radial growth of beech, Douglas fir and spruce: Differences between pure and mixed stands reveal complementarity between species - Johan Bärwald; Kerstin Pierick; Christian Ammer; Roman Mathias Link; Christina A. Hackmann (Agricultural and Forest Meteorology, 2026)

Artificial gaps but not thinning persistently enhance forest structural heterogeneity - Kerstin Pierick; Roman Mathias Link; Heidi Linda Inderwies; Stephanie Puggaard Koolen; Biyun Wu; Bernhard Schuldt; Jörg Müller; Christian Ammer; Dominik Seidel (European Journal of Forest Research, 2026)
The strong focus on wood production has led to structural homogenization of managed forests worldwide, reducing habitat heterogeneity and thereby β-diversity of forest dwelling taxa. The Enhanced Structural Beta Complexity (ESBC) approach aims to counteract this by actively creating a heterogeneous structural mosaic in production forests. This is achieved by applying combinations of different deadwood retention treatments and spatial timber removal patterns (thinning vs. gaps) in neighboring forest patches. In a field experiment, heterogeneous ESBC-treated forest districts (10–20 ha) were implemented in temperate broad-leaf forests and paired with homogeneous control districts. Heterogeneity in the ESBC districts was created by applying 15 treatments in forest patches of 50 m × 50 m. The treatments combined cutting 30% of the stand basal area, either regularly distributed throughout the whole patch (thinning) or aggregated in the patch center (gap), with deadwood retention. We quantified the changes of forest structure in 90 forest patches using a 7-year time series of repeated terrestrial laser scanning and calculated three indices: stand structural complexity index, understory complexity index, and canopy openness. While thinning had only minor effects, the removal of equal amounts of timber through gap felling greatly affected all structural indices. In canopy gaps, structural development was highly dynamic between years and impacted by deadwood retention treatments. Mostly driven by the pronounced structural changes in canopy gaps, ESBC treatments effectively lead to structurally heterogeneous forests throughout the post-intervention period. Therefore, the ESBC approach is a promising tool for integrating biodiversity conservation in multifunctional forests.

Reed between the lines: Terrestrial 3D laser scanning to assess recreational impacts on lakeshore vegetation - Nora Meyer; Matthias Kunz; Roman Mathias Link; Goddert von Oheimb (Limnologica, 2025)